2007
DOI: 10.1001/archinte.167.19.2080
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Cereals and Risk of Heart Failure in the Physicians' Health Study I

Abstract: Background: Heart failure (HF) is the leading cause of hospitalization among the elderly population in the United States. Consumption of grain products and dietary fiber has been shown to reduce the risk of hypertension and myocardial infarction. However, it is not known whether a higher consumption of breakfast cereals is associated with risk of HF. Methods: This study evaluated prospectively the association between breakfast cereal intake and incident HF among 21 376 participants of the Physicians' Health St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 36 publications
5
38
0
1
Order By: Relevance
“…An increase of 3 servings total whole grains/d was associated with a 17% lower risk of mortality from all causes, a 25% lower risk of mortality from CVD, and a 10% reduced risk of total-cancer mortality. Similar to our findings, accumulating evidence from observational studies has shown significant inverse associations between whole-grain intake and risk of incident CVD (51)(52)(53). A meta-analysis of 7 cohort studies also revealed that greater whole-grain intake (2.5 servings/d compared with 0.2 servings/d) was associated with a 21% lower risk of CVD events (5).…”
Section: Discussionsupporting
confidence: 89%
“…An increase of 3 servings total whole grains/d was associated with a 17% lower risk of mortality from all causes, a 25% lower risk of mortality from CVD, and a 10% reduced risk of total-cancer mortality. Similar to our findings, accumulating evidence from observational studies has shown significant inverse associations between whole-grain intake and risk of incident CVD (51)(52)(53). A meta-analysis of 7 cohort studies also revealed that greater whole-grain intake (2.5 servings/d compared with 0.2 servings/d) was associated with a 21% lower risk of CVD events (5).…”
Section: Discussionsupporting
confidence: 89%
“…Sixteen prospective studies were included in the meta-analysis for consumption of whole grains (16 reports) (Del Gobbo et al 2015;Djousse and Gaziano 2007;Hansen et al 2017;Helnaes et al 2016;Jensen et al 2004;Liu et al 2000b;Liu et al 1999;Mizrahi et al 2009;Muraki et al 2015;Neelakantan et al 2016;Nettleton et al 2008;Rautiainen et al 2012;Sonestedt et al 2015;Steffen et al 2003;Tektonidis et al 2015Tektonidis et al , 2016 (Supplemental Table 2), 9 studies for refined grains (8 reports) (Djousse and Gaziano 2007;Eshak et al 2014;Liu et al 2000b;Mizrahi et al 2009;Muraki et al 2015;Sonestedt et al 2015;Steffen et al 2003;Yu et al 2013) (Supplemental Table 3), 35 for vegetables (32 reports) (Belin et al 2011a;Bendinelli et al 2011;Bhupathiraju et al 2013;Buckland et al 2009;Dauchet et al 2004;Del Gobbo et al 2015;Dilis et al 2012;Gillman et al 1995;Hansen et al 2017;Hansen et al 2010;Hirvonen et al 2001;Johnsen et al 2003;Joshipura et al 1999;Keli et al 1996;…”
Section: Resultsmentioning
confidence: 99%
“…Reports from the Physicians' Health Study (76,79) limited the investigation to breakfast cereals containing whole grains and $25% bran. All 9 reports from 4 large and 1 small prospective cohort studies showed significant inverse associations between intakes of mixtures of whole grains and bran and risks of CVD mortality, CVD events, and heart failure in both males and females (Table 9; 13-15, 45, 76-79).…”
Section: Studies On Mixtures Of Whole Grains and Branmentioning
confidence: 99%